« Leave it or take it away »: ethical considerations on the removal of overpaintings - Maximiliaan P.J. Martens (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
During the current conservation of the Ghent Altarpiece, carried out by a team of KIK-IRPA, a large amount of old overpaint has been discovered. These are studied with a number of innovative analytical techniques. It is argued here that the introduction of these techniques allows for a re-evaluation of the conservation theoretical and ethical dimensions of coping with such phenomena.